The evolving multilayered global financial safety net: The case of the Association of Southeast Asian Nations+3 regional sinancial safety net and the International Monetary Fund - Pradumna Bickram Rana (Asian Development Bank Institute (ADBI), 2017)
This paper argues that in the aftermath of the global economic crisis, the centralized international monetary architecture or the global financial safety net (GFSN) set up at the Bretton Woods conference is evolving towards a more decentralized multilayered safety net comprising (i) the G20 at the apex as an overarching institution, (ii) multilateral financial safety nets (MFSNs) established under the auspices of the International Monetary Fund (IMF), (iii) bilateral financial safety nets (BFSNs) among central banks, (iv) regional financial safety nets (RFSNs) established in various regions of the world, and (v) national financial safety nets (NFSNs) or reserve accumulation by individual countries. The most significant factor explaining this evolution is financial globalization and the increased incidence of capital account crisis. As in many other regions of the world, Asia has established the ASEAN+3 RFSN, comprising the Chiang Mai Initiative Multilateralization (CMIM) and ASEAN+3 Macroeconomic Research Office (AMRO), for crisis prevention and management. The ASEAN+3 RFSN seeks to complement the IMF. However, because of its ad hoc nature and the relatively small size and cumbersome disbursement procedures, it is unlikely that this facility will be utilized when the next financial crisis hits the region. Based on Europe's experience with RFSN and IMF cooperation, the paper makes the case for a more structured form of cooperation between the ASEAN+3 RFSN and the IMF. Our proposal, together with the recent upgradation of AMRO to an international organization, could greatly enhance the effectiveness of the ASEAN+3 RFSN.
Keywords: F3; F33; 330; Finance sector development; Governance and public sector management